2010
DOI: 10.1007/s11571-010-9134-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning with perceptions

Abstract: In this work we present an approach to understand neuronal mechanisms underlying perceptual learning. Experimental results achieved with stimulus patterns of coherently moving dots are considered to build a simple neuronal model. The design of the model is made transparent and underlying behavioral assumptions made explicit. The key aspect of the suggested neuronal model is the learning algorithm used: We evaluated an implementation of Hebbian learning and are thus able to provide a straight-forward model capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Biological mechanisms of learning, including OL, have been studied in the context of perceptual processing, see, e.g. (Stemme et al 2011;Neiman and Loewenstein 2013). The idea of vague-to-crisp transitions found support in previous neuroimaging studies in the field of visual processing (Bar et al 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 85%
“…Biological mechanisms of learning, including OL, have been studied in the context of perceptual processing, see, e.g. (Stemme et al 2011;Neiman and Loewenstein 2013). The idea of vague-to-crisp transitions found support in previous neuroimaging studies in the field of visual processing (Bar et al 2006).…”
Section: Conclusion and Discussionmentioning
confidence: 85%
“…Indeed, investigations across the human cutaneous somatosensory system have shown that the evoked responses of cutaneous mechanoreceptors to physical stimulus were consistent with the psychophysical responses (Johnson et al 2002), and then the present result indicated that the built fabric-skin-receptors model predicted the typical neural behavior of SAIs cutaneous mechanoreceptors and the typical tactile responses. Here, the comparison between sensory responses and neural responses neglected the perceptual learning (Stemme et al 2011).…”
Section: Simulationmentioning
confidence: 99%